Scenario of insect pests, predators and pollinators associated with crop plants in an agroforestry in Bangladesh (SAARC Journal of Agriculture, 2019)
The abundance of insect pests, predators and pollinators and status of pest insects associated with citrus, mango and pineapple crops grown in an agroforestry in Bangladesh was studied during July 2015 to June 2016. Twenty five species of insects belonging to 19 families in 5 orders were found as pest of citrus and their relative abundance varied from 2.4 to 13.4%. Among the citrus pests, green leaf hopper was most abundant, but whitefly, mealy bug, lemon butterfly and leaf minor were found as major pests. Fifteen species of insects under 13 families in 6 orders were found as pests of mango and their relative abundance varied from 0.5 to 82.6%, and hopper and fruit fly were found as major pests. Four species of insects belonging to 4 families in 3 orders were found as pest of pineapple and their relative abundance varied from 12.2 to 44.9%, and all were found as minor pests. There were 20 species of predator insects belonging to 13 families in 6 orders and their abundance ranged from 0.8 to 2.5/ 40 sweeps. In total 19 species of insects belonging to 12 families in 4 orders were found as pollinators and their abundance varied from 1.7 to 5.1/40 sweeps. The ants and honeybees were most abundant as predators and pollinators, respectively.SAARC J. Agri., 17(1): 13-22 (2019)